THE EFFECT OF PHILOSOPHY FOR CHILDREN'S (P4C) APPROACH ON PRIMARY SCHOOL STUDENTS' ATTITUDE TOWARDS SCIENCE AND PROBLEM-SOLVING SKILLS - Aksoy, Muhammed; Uğraş, Mustafa (Tuğba YELKEN, 2024)
This study investigated the effect of the Philosophy for Children (P4C) Approach, one of the most effective ways to help children who enjoy thinking and questioning from an early age, gain thinking skills, and make sense of what they think, on primary school students' attitudes towards science and problem-solving skills. The Philosophy for Children implementation process was carried out for 7 weeks and 3 hours in each lesson, 21 hours in total, with the experimental and control groups selected from 4th grade students studying in a public school in Haliliye district of Şanlıurfa province. This process was conducted using a mixed-methods research method. This study preferred to use the explanatory sequential mixed research method, as it collected qualitative data after analyzing quantitative data. The study employed a quasi-experimental design in the quantitative dimension, incorporating a pretest-posttest control group. The qualitative dimension of the study employed a case study for in-depth data analysis. The variables related to the effect of the Philosophy for Children approach on primary school students' attitudes towards science and problem-solving skills were carefully examined, and the findings were interpreted. The findings concluded that the Philosophy for Children Approach, through its activities and practices, positively influenced the 4th grade students' attitudes towards science and problem-solving skills
Keywords: Learning Sciences; Öğrenme Bilimleri